If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 + -2(2a + 1) = 6w + -2(6 + w) Reorder the terms: 22 + -2(1 + 2a) = 6w + -2(6 + w) 22 + (1 * -2 + 2a * -2) = 6w + -2(6 + w) 22 + (-2 + -4a) = 6w + -2(6 + w) Combine like terms: 22 + -2 = 20 20 + -4a = 6w + -2(6 + w) 20 + -4a = 6w + (6 * -2 + w * -2) 20 + -4a = 6w + (-12 + -2w) Reorder the terms: 20 + -4a = -12 + 6w + -2w Combine like terms: 6w + -2w = 4w 20 + -4a = -12 + 4w Solving 20 + -4a = -12 + 4w Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -4a = -12 + -20 + 4w Combine like terms: 20 + -20 = 0 0 + -4a = -12 + -20 + 4w -4a = -12 + -20 + 4w Combine like terms: -12 + -20 = -32 -4a = -32 + 4w Divide each side by '-4'. a = 8 + -1w Simplifying a = 8 + -1w
| x+y+5z=-8 | | 3.1n-0.03=-9 | | 6(x+24)(x-6)+3(x+12)(x-18)=19(x+45)-(x-36) | | 5w^7/w6 | | 15=18+t | | 6(x+24)(x-6)+3(x+12)(x-18)=18(x+45)-(x-36) | | Y=-21+3 | | 4x-7=-95 | | 21.6-a=5d | | x^2+4x-8160=0 | | 6(x+5)(x-2)+3(x+10)(x-18)=18(x+50)-(x-36) | | 9=w/35 | | 1.6/3.2=2.8/t | | k+-7=-3 | | -11=5y+12-4y-1 | | W/15=7/2 | | 6.6/1.2=w/4.2 | | -4+7x+-12x^2+21x^3=0 | | g+-5=-17 | | W/15=7/15 | | a+8=11-2a | | 8mn+9p=7k | | 4(-6x+7)=-212 | | 3(8x-1)-4x=17 | | 15/a=25/14 | | (x+2+3i)(x+2-3i)= | | 3d+4=2+3-.5 | | 10r^2-17r+6=0 | | -96-2x=129-11x | | 2(3a-1)=14 | | 8x+x-8+14=24 | | 87x^3-65x^3=12x^3 |